Democracy to come: Active forums as indicator suites for e-participation and e-governance - Rodan, D.; Balnaves, Mark (Springer, 2009)
There is in modern industrial societies a 'civic deficit' Civic engagement in the traditional sense of community values and civic participation is declining (Putman 2000). What has not been examined is the ways in which various media including new media may provide real options for participatory cultures and participatory democracy now and in the future. Undoubtedly there are differences between participatory cultures that are considered a `genuine' contribution to representational democracy and those that are not. This paper, based on initial research into Internet activism, will examine GetUp! as a specific example of an active forum that the authors argue enable participatory citizenship through media participation. While there are very few examples of active forums that might be considered a 'genuine' contribution to representational democracy there are clear signals that activism through active forums is maturing into a potent democratic force.